Industrial Hunting and Fishing in the Far North: Labor and Everyday Life of Yakutia’s Hunters, 1960s–1980s - Svyatoslav I. Fedorov; Liliya I. Vinokurova (Oriental Studies)
Introduction. In the Far North, where harsh climate conditions and underpopulation pose specific challenges to human life, hunting remains an important economic activity. The study of labor and daily life of Yakutia’s hunters provides further insights into the specifics of human adaptation to severe environments and evaluates the contribution of hunters to the region’s development. Goals. The article attempts an analysis into the labor agenda and everyday life of hunters in Yakutia throughout the 1960 to 1980s. To facilitate this, the paper shall investigate the impacts of state policies on hunting arrangements, examine some peculiarities of hunting in the Far North, identify key essentials of their daily (mostly autonomous) work. Materials and methods. The study examines a variety of materials that secure a comprehensive understanding of labor and daily routine of hunters in the 1960s to 1980s. These include documents from state and departmental archives containing data on the development of industrial hunting in Yakutia, working and socioeconomic conditions for hunters, a significant supplement thereto be interviews with hunters proper and their life stories. Special attention is paid to local history works and oral narratives of small villages where hunting remains an important part of the life-support system to date. The research is based on an integrated approach that comprises analyses of historical sources, comparative evaluations, use of ethnographic and oral history tools. Results. The sources have proved instrumental in outlining the daily life of hunters, their working routine, problems and challenges they faced. From the 1960s to late 1980s, hunting and animal husbandry were important sectors of the Soviet economy. Those would bring the so much required income and currencies to the government, which is confirmed by constant attention of highest agencies to hunting arrangements and management. So, hunting was considered an independent and important branch of the national socialist economy. The examined period witnessed a number of important steps aimed at supporting the activity in the Yakut ASSR. The work of hunters was necessary for the state, but it was as needed by indigenous populations since hunting remained an integral part of their life sustenance.